Subsequent events: key challenges in financial reporting - Mohd Rodzi, Nor Kartini; Naiimi, Nazirah; Abdul Rahman, Norshimah (Faculty of Accountancy, 2024)
A transparent view of corporate financial reporting helps in identifying potential issues, making strategic decisions, and ensuring compliance with financial regulations. According to Zatravina & Nezametdinova (2022), company financial reporting provides stakeholders with relevant and reliable accounting information about the company's financial position, financial performance and changes in cash flows, ensuring successful economic interaction and cooperation. The purpose of financial reporting is to deliver financial information that benefits the stakeholders, lenders and other creditors in making investment decisions about the provision of economic resources to the reporting entity (Anwar et al. 2022). The provided financial information should be accurate and reliable, giving them a complete understanding of the company's financial state, progress, and any changes that have occurred. Furthermore, Maines & Wahlen (2006) stated that the reliability of accounting information is useful for decision making process, representing the extent to which the financial information is neutral, free from error, and a faithful representation. This enables stakeholders to make informed decisions about investments, lending, or other financial commitments. This article addresses the challenges and possible outcomes associated with subsequent events which are part of accounting information that is crucial for enhancing the accuracy, transparency, and reliability of financial statements of companies.